انتشار عوز Vit B12 عند مرضى الداء السكري نمط 2 المعالجين بالميتفورمين - قبلان, يونس; حمدان, ربا (Latakia University Journal -Medical Sciences Series, 2013)
شملت الدراسة 184 مريضاً من مرضى الداء السكري نمط 2 المراجعين العيادة الاختصاصية أو المرضى المقبولين في أقسام مشفى الأسد الجامعي بدمشق خلال عامي 2012-2013. تمّ تقسيم المرضى إلى ثلاث مجموعات: المجموعة A: وهي مجموعة المرضى السكريين غير المعالجين بالميتفورمين وعددهم 72 مريضاً (39,1%)، والمجموعة B: وهي مجموعة المرضى السكريين المعالجين بالميتفورمين لمدة تزيد عن 18 شهراً وعددهم 72 مريضاً (39,1%)، و المجموعة C: وهي مجموعة المرضى السكريين المعالجين بالميتفورمين لمدة تقل عن 6 أشهر وعددهم 40 مريضاً (21,8%). وقد بيّنت الدّراسة أن 43,5% من المرضى لديهم عوز Vit B12 إذ تطوّر لدى 32,6% من المرضى السكريين المعالجين بالميتفورمين العوز بالمقارنة مع 10,9 من المرضى غير المعالجين بالميتفورمين. كما تمّ تقسيم المرضى المعالجين بالميتفورمين (112مريضاً) حسب الجرعة المتناولة ثمّ حسب مدّة العلاج إلى مجموعتين لكل فئة وتبيّن وجود علاقة ارتباط عكسيّة بين مدّة العلاج بالميتفورمين وجرعته ومستويات Vit B12. وقد وجدنا أيضاً أنّه على الرّغم من زيادة خطورة حدوث عوز Vit B12 عند المرضى السكريين المعالجين بالميتفورمين فإنّ هذا لم يترافق مع حدوث الأعراض مثل فقر الدم العرطل والأعراض العصبية. The study included 184 patients with type 2 diabetes referred to the specialist clinic or admitted in the sections of Al-Assad University Hospital in Damascus during the years 2012-2013. The patients were divided into three groups: Group A: a group of patients with diabetes is not treated with Metformin, 72 patients (39,1%). Group B: a group of patients with diabetes is treated with Metformin for more than 18 months, 72 patients (39,1%). Group C: a group of patients with diabetes is treated with Metformin for less than 6 months, 40 patients (21,8%). This study showed that 43,5% of the patients have Vit B12 deficiency: 32,6% of patients with diabetes treated with Metformin compared with 10,9% non treated with Metformin. The patients who were treated with Metformin (112 patients) were divided by dose intake and then depending on the duration of treatment into two groups for each category and shown an inverse correlation between duration and dose of therapy with metformin and levels of Vit B12. We also found that despite the increased risk of Vit B12 deficiency in patients with diabetes treated with Metformin but this was not associated with the occurrence of symptoms such as megaloplastic anemia and neurological symptoms.